Maternal and perinatal outcomes by planned place of birth in Australia 2000 – 2012: a linked population data study. Issue 10 (29th October 2019) - Homer, Caroline S E; Cheah, Seong L; Rossiter, Chris; Dahlen, Hannah G; Ellwood, David; Foureur, Maralyn J; Forster, Della A; McLachlan, Helen L; Oats, Jeremy J N; Sibbritt, David; Thornton, Charlene; Scarf, Vanessa L
Abstract : Objective: To compare perinatal and maternal outcomes for Australian women with uncomplicated pregnancies according to planned place of birth, that is, in hospital labour wards, birth centres or at home. Design: A population-based retrospective design, linking and analysing routinely collected electronic data. Analysis comprised χ 2 tests and binary logistic regression for categorical data, yielding adjusted ORs. Continuous data were analysed using analysis of variance. Setting: All eight Australian states and territories. Participants: Women with uncomplicated pregnancies who gave birth between 2000 and 2012 to a singleton baby in cephalic presentation at between 37 and 41 completed weeks' gestation. Of the 1 251 420 births, 1 171 703 (93.6%) were planned in hospital labour wards, 71 505 (5.7%) in birth centres and 8212 (0.7%) at home. Main outcome measures: Mode of birth, normal labour and birth, interventions and procedures during labour and birth, maternal complications, admission to special care/high dependency or intensive care units (mother or infant) and perinatal mortality (intrapartum stillbirth and neonatal death). Results: Compared with planned hospital births, the odds of normal labour and birth were over twice as high in planned birth centre births (adjusted OR (AOR) 2.72; 99% CI 2.63 to 2.81) and nearly six times as high in planned home births (AOR 5.91; 99% CI 5.15 to 6.78). There were no statistically significant differences in the proportion of intrapartum stillbirths, early or late neonatal deaths between the three planned places of birth. Conclusions: This is the first Australia-wide study to examine outcomes by planned place of birth. For healthy women in Australia having an uncomplicated pregnancy, planned births in birth centres or at home are associated with positive maternal outcomes although the number of homebirths was small overall. There were no significant differences in the perinatal mortality rate, although the absolute numbers of deaths were very small and therefore firm conclusions cannot be drawn about perinatal mortality outcomes.